THE ROLE OF THE LIQUIDITY COVERAGE RATIO AND HIGH-QUALITY LIQUID ASSETS PORTFOLIO IN MANAGING BANK LIQUIDITY (International Congress on Economics, Management and Business Studies, 2026)
In the context of global financial instability, digital transformation and the rapid expansion of real-time payment systems, effective liquidity management has become one of the most important conditions for maintaining the solvency and financial stability of commercial banks. Modern banking activity is increasingly exposed to rapid deposit movements, interest rate volatility, market liquidity shocks and changes in customer behaviour. In such circumstances, banks are required not only to hold sufficient capital, but also to maintain an adequate stock of highly liquid assets that can be converted into cash quickly and without significant loss of value.